History and memory in Maria Rosa Lojo (Tribute to Marilene Weinhardt) - Esteves, Antonio R. [UNESP] (Univ Federal Parana, Editora, 2016)
For more than three decades Marilene Weinhardt has been dedicating her studies to the hazy relationship between historical and fictional discourse, trying to draw a map of the boundaries between literature and history. In this sense, she made a strong reflection on the issue, from theoretical texts originating from various places, channeling them to the Latin American reality, in the case of those produced in other contexts. The most significant contribution, however, is its application in the reading of an important body of literature produced in recent decades within the Brazilian literature. Such readings, more than understanding the intricate thematic (and formal) relations, between literature and history, try to give account of the facets of the Brazilian reality and contribute to the definition of smoky contours of national identity (weinhardt, 2002, p. 158). From this theoretical legacy, this paper makes a panoramic reading of the work of Maria Rosa Lojo (1954), following the tracks of the historical element and the Argentine cultural memory presented in the writer's work. Daughter of exiled Spanish parents who settled in Argentina where she was born in an interesting cultural in-between, she has been producing for three decades a multifaceted work that circulates between fiction, history and memory, a varied texture of form and themes. Reading Maria Rosa Lojo from the perspective of critical thinking of Marilene Weinhardt is a comparative literature exercise that enriches the thought of these two distinguished Latin Americans demonstrating that the platinum cultural integration is no longer a dream but becomes a vibrant reality.
Keywords: historical fictional narrative; literature; memory; history; Maria Rosa Lojo